O lugar da filosofia na formação e no reconhecimento dos sujeitos da EJA - Vinícius Figueiredo Costa (2019)
This dissertation presents the results of the research about the place of Philosophy in the formation and recognition of the right, citizenship and autonomy of the subjects of Youth and Adult Education (EJA), from a study about the philosophical experiences of the classes. Youth and Adult High School Project (PEMJA-UFMG) from 2009 to 2018 in the city of Belo Horizonte. It also presents a relationship between theoretical and methodological assumptions in philosophy teaching studies, the history of the Technical College Youth and Adults program (COLTEC-PEMJA) and an analysis of philosophy teaching in the ten years of compulsory content teaching. offered by this program and the impacts on its students. As methodological procedures, a questionnaire with ten closed questions was applied to at least two studies of each year that studied in the PEMJA Project from 2009 to 2018, in order to constitute a general picture of the profile of these classes and the studied studies, as well as the students' perceptions about their philosophical experiences in Youth and Adult Education. Still, based on a theoretical-methodological framework that considers the protagonists of their experiences, and following the research assumptions, five studies were interviewed, distributed over the last years of the project, in order to understand more deeply the motivations that led to the learned results. In general research, through the analysis and interpretation of students' narratives about PEMJA and the Philosophy classes taught. As the results, understand that there is a difficulty in the perception of EJA students about their citizenship, autonomy and social rights related to learning in EJA classrooms at the same time that these characteristics are displayed in the daily life of students after years of education in Youth and Adult Education.